Perception of family members after family meeting in palliative care provided by family physicians. - ศุภศิริสันต์ ญาณิศา; Manomaipiboon ฺBasmon; จงเจษฎ์ ธนกร (Journal of Primary Care and Family Medicine (PCFM), 2023)
Introduction: Family meetings are an essential component of palliative care to provide treatment goals between patient, family and health care provider. Communication is also a fundamental component to establish an understanding of the care plan. SPIKES protocol framework for family meetings were done in the palliative care unit to generate treatment goal. Evaluation of SPIKES protocol framework for family meeting efficacy would guide us to improve the family meeting in our practice. This study aims to assess family members’ perceptions of process in family meeting in palliative care compared with family physicians’ perceptions. Design: A cross-sectional study Methods: To examine family members perceptions’ and family physicians’ perceptions during a family meeting by using the SPIKE protocol. A total of 100 family member participants were enrolled. A questionnaire survey was applied based on six attributes derived from the SPIKES protocol. Results: There was moderate to excellent level of agreement between family physicians’ and family members’ perceptions in family meeting in palliative care. (κ = 0.3902 - 0.8837, % agreement = 96-99 %, p < 0.001) While, discrepancies were more evident in issues involving emotion. The satisfaction level of family members in family meeting was in excellent level. Conclusion: SPIKES protocol framework for family meeting could guide family physicians and family members to establish goals of care for palliative patients with more empathy. In order to create an understanding between physicians and family members, the SPIKES protocol could bring satisfaction to the family meeting. Keywords: family meeting, palliative care, SPIKES protocol